RESPON IMUN MUKOSA DAN SELULER PADA TIKUS YANG DIBERI BUBUK SUSU KAMBING DENGAN INFEKSI Salmonella Typhimurium [Mucosal and Cellular Immune Response of Rat Given Goat Milk Powder and Infected with Salmonella Typhimurium] - . Nurliyani; Madarina Julia; Eni Harmayani; Endang Baliarti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
ABSTRACT Goat milk contains bioactive proteins and oligosaccharides which can act as immunomodulators and prebiotics respectively. The objectives of this study were to determine the effect of giving goat milk powder on mucosal immune response (sIgA/secretory immunoglobulin A), cellular immune response (IFN-γ/interferon-γ) and the total number of lactobacilli in caecal digesta of infected rat by Salmonella Typhimurium. Male Sprague Dawley rats 3 weeks old were divided into two groups: 1) goat milk powder treatment, and 2) control. After 14 days given goat milk powder, the rats were infected with Salmonella Typhimurium and after 21 days were killed. The results showed that the average concentration of sIgA in group of rats given with goat milk powder was not significantly different with the control rat (42.95 ng/ml). The concentration of IFN-γ in rat given with goat milk powder was significantly different (63.33 pg/ml) from the control (45.00 pg/m) (p